GGasCT: bringing formal methods to the computational thinking - Silva Júnior, Braz Araujo da (2020)
This work presents an alternative approach for developing computational thinking. Several definitions for computational thinking related terms are given in order to undo the terminological issues the area admittedly has, each of those terms are explored and clarified individually. The selection of the terms draws on a systematic literature review that sheds a light on the most commonly addressed terms in the computational thinking literature. A visual and formal language, the graph grammar, is introduced, formally defined and presented as a proper approach for fostering the computational thinking skills described in this thesis. Relations between the formalism and the skills are discussed, an educational game and a game engine are offered as examples of graph grammars being used in education, specially k-12. To guide the development and application of those tools, education and educational games theories such as theory of Flow and Bloom’s Taxonomy, and methodologies such as the ENgAGED and MEEGA+ methods are used. As results a complete and comprehensive framework for developing and assessing computational thinking through graph grammars is theoretically grounded and has its practice exemplified by experience reports of uses of the educational game.